PEMBUATAN DAN UJI ORGANOLEPTIK SEDIAAN MINUMAN SERBUK INSTAN DAUN PEPAYA (Carica papaya L.) DAN KACANG HIJAU (Vigna radiata L.) UNTUK MEMPERLANCAR PRODUKSI AIR SUSU IBU (ASI) - Widianto, Diaz Ananda; Yanto, Elih Sutisna; Handayani, Reti Puji (Sekolah Tinggi Ilmu Kesehatan Holistik, 2020)
Background: Breastmilk is an emulsion of fat in a solution of protein, lactose and organic salts secreted by the mother's breast glands as the baby's main food. Currently, many mothers give breast milk for less than six months due to several factors such as sick babies, tired work and stress, so that milk production is not smooth and others. Papaya leaves contain several important nutrients, several studies have been conducted, Entin (2002) proved that katuk leaves, bitter melon leaves, and papaya leaves are complementary plants which are traditional plants and have the potential to increase breast milk production4. Mung beans also contain active compounds, namely polyphenols and flavonoids which function to increase breast milk production hormones. organoleptic tests for three weeks using papaya (Carica papaya L.) and green beans (Vigna radiata L.) to facilitate the production of breast milk (ASI) by making it easy and practical. Methods: This study used an action research design. Preparations with different sugar formulations, namely F1 5 grams of papaya leaves, 41.6 grams of green beans, 60 grams of sugar. F2 5 grams of papaya leaves, 41.6 grams of green beans, 90 grams of sugar. And F3 5 grams of papaya leaves, 41.6 grams of green beans, 120 grams of sugar. Samples are stored in the same storage, namely at room temperature 20-250C. Results: It showed that the papaya and green bean instant powder drink dosage stored at room temperature 20-250C had organoleptic stability of shape, odor, and color. Conclusion: From the results of the organicoleptic test, 3 preparations with slightly different tastes were produced, one of which has a better taste, namely the taste is not too sweet and not too bitter. This preparation can last for three weeks with a relatively unchanged physical condition.